Numerical Study on the Effect of Convection on Grain Growth Structure in Metallic Systems - Kohei Tanimoto; Nagano Hideaki; Kenjiro Shimano; Suguru Shiratori (Proceedings of the 8\(^th\) International Conference on Solidification and Gravity, 2025)
The effect of convection within the droplet during the levitation experiment on the grain structure was investigated using phase-field simulation considering convection. This study aims to distinguish the effects of convection and heterogeneous nucleation on the grain structure. In binary alloy systems, convection generates a strong solute gradient near the solid-liquid interface, leading to faster solid growth. The effect of flow velocity on the degree of grain deformation was investigated based on elliptical fitting and aspect ratio, and it was found that the shape of grown grains tends to deform with an increase in convection velocity. Under levitation experimental conditions, the aspect ratio decreased up to 0.80 times compared to the no-flow case. Small vortices are generated for the further large velocity, creating the local concentration gradient, thus resulting in the short-wavelength grain interface. In the solidification of pure metals based on heat transport, the effect of convection on grain shape was relatively small compared to the case of binary alloys because of the large thermal diffusion.